Human Relations and Organizational Climate and Its Influence on Employee Morale of PT. Matrix Primatama Bandung - Wawan Hermawan; Rizky Ferrari Oktavian; Ginanjar Wira Saputra (Program Studi Administrasi Bisnis, STIA Bandung, 2023)
The purpose of this study is to examine the influence of Human Relations and Organizational Climate on Employee Morale. This research uses a sample of 96 employees working at PT. Matrix Primatama Bandung, using descriptive and verification methods. The data collection technique employed by the researcher involves primary and secondary data sources in the form of questionnaires distributed to employees at PT. Matrix Primatama Bandung. The analysis used is path analysis with the assistance of SPSS software and hypothesis testing. The results of this study indicate that the Human Relations variable is considered good, Organizational Climate is considered good, and Employee Morale is considered good. The verification results reveal that Human Relations has an impact on Employee Morale, Organizational Climate has an impact on Employee Morale, and there is an influence of Human Relations and Organizational Climate on Employee Morale at PT. Matrix Primatama Bandung.